New skills and their certification: developments in Europe and Italy - Benussi, Fulvio Oscar (Community Notebook. People, Education and Welfare in the Society 5.0, 2024)
In order to promote the implementation of more flexible and modular learning pathways in the countries of the European Union, to contribute to innovation towards more inclusive and sustainable systems also through the modernisation of education and training systems, and to facilitate mobility in the labour market, the European Council proposed the use of microcredentials. An effective culture of lifelong learning is crucial for everyone to possess the knowledge, skills and competences they need to thrive in their personal and professional lives. A micro-credential is evidence of the results an individual has acquired through a short learning experience. Learning outcomes must have been assessed against transparent and clearly defined standards. Microcredential learning experiences are designed to provide the learner with specific knowledge, skills and competences that meet personal, cultural, professional or labour market needs.